Silver nanoparticles synthesized using Tualang honey ameliorate seizures, locomotor activity, and memory function in KA-induced status epilepticus in male rats - Hasim, Hidani; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Rao, Pasupuleti Visweswara; Muthuraju, Sangu; Muzaimi, Mustapha; Asari, Mohd Asnizam (BioMedPress, 2022)
Introduction: In recent years, green synthesis of silver nanoparticles using natural products has been increasingly utilized in the biomedical field as a therapeutic approach for managing neurodegenerative diseases. This study aimed to determine the effects of silver nanoparticles synthesized using Tualang honey (THSN) on seizure activity and locomotor and memory functions in rats after kainic acid (KA) induction. Methods: Male Sprague Dawley rats were randomly divided into sixg roups (n = 6/group), and each group was pre-treated orally with either distilled water or THSN (10mg/kg or 50mg/kg), according to their respective groups. Each rat was injected subcutaneously with KA (15 mg/kg) or saline after the last pre-treatment, and the onset of the first generalized seizure was recorded. After 24 hours and five days of KA induction, an open field test (OFT) and a novel object recognition test (NORT) were performed before they were sacrificed. Results: THSNpre-treatment of KA-induced status epilepticus groups demonstrated an increment in latencies to the onset of the first generalized seizure and the number of line crossings in OFT, with a higher recognition index of NORT compared to the untreated KA-induced status epilepticus group. Conclusion: THSN could have neuroprotective effects in ameliorating seizures, locomotor activity, and memory function after KA-induced status epilepticus in male rats.